Pengaruh Pemasaran Berbasis ICT Terhadap Volume Penjualan Produk Kuliner UMKM Bandar Lampung - Elvira, Dhenita; Surya, Andi; Yudhinanto , Yudhinanto; Renandi , Renandi; Alie, Maria Septijantini; Hasbullah , Hasbullah; Oktaria, Eka Travilta (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This resealrch alims to determine the influence of the use of ICT-balsed malrketing straltegies represented by the use of sociall medial, e-commerce, mobile malrketing alnd e-palyment on salles volume. Methodology/alpproalch: The resealrch method used is al qualntitaltive method with multiple linealr regression alnallysis. The populaltion, nalmely MSMEs in the MDH community in Balndalr Lalmpung City with al 72 salmple, wals selected using the method purposive salmpling. Hypothesis testing with the coefficient of determinaltion, F test alnd t test. Previously, instrument tests were calrried out, alnd clalssicall alssumption tests. Results/findings: The research results show that the marketing strategy implemented can have a positive influence in increasing sales volume when using social media variables, e-commerce and e-payment. But, in use mobile marketing by UMKM MDH the results did not have a significant effect. Conclusions: Regression analysis showed that while ICT-based marketing strategies (social media, e-commerce, mobile marketing, and e-payment) were expected to influence sales volume, mobile marketing (X3) had no significant partial effect. Limitaltions: This resealrch is limited to the influence of ICT-balsed malrketing straltegies with the use of sociall medial, e-commerce, mobile malrketing alnd e-palyment by MSMEs in the MDH community of Balndalr Lalmpung city for period of 1 yealr. Contribution: This resealrch is useful for MSMEs, it caln increalse understalnding of the benefits of ICT-balsemalrketing straltegies to increalse salles volume in the current eral of digitall, provide guidalnce in selecting alnd implementing alpproprialte ICT-balsed malrketing straltegies, Enrich the repertoire of resealrch knowledge for the UMITRAL